The Relationship between Pregnancy Spacing and Parity with Incidence of Chronic Energy Deficiency (CED) in Pregnant Women - Usi Lanita; Sri Astuti Siregar; Kasyani Kasyani (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
One of the nutritional problems in pregnant women that is important to address is Chronic Energy Deficiency (CED). CED can cause anaemia, bleeding, the mother does not gain weight normally, and contracting infectious diseases. This study aims to determine the relationship between pregnancy spacing and parity with the incidence of CED in pregnant women. Quantitative research with cross-sectional design. The study was conducted on pregnant women in Jambi City in 2024, totalling 98 people. Data analysis using Chi Square test. The results showed that there was a significant relationship between pregnancy distance (0.034) with the incidence of CED in pregnant women. There is no relationship between parity (0.340) with the incidence of CED in pregnant women. It is concluded that there is a relationship between pregnancy spacing and the incidence of SEZ in pregnant women. It is expected for pregnant women to set a safe pregnancy distance that is above 2 years from the previous pregnancy, in addition it is also recommended to the Health Office and Puskesmas to often educate to increase the knowledge of pregnant women about the prevention and treatment of CED.